Confederation debt management since 1970 - Basil Guggenheim; Mario Meichle; Thomas Nellen (Swiss Journal of Economics and Statistics, 2019)
This paper analyzes the Confederation's debt management. The Confederation actively manages roll over and interest rate risk by increasing bond maturity with increasing marketable debt-to-GDP levels. It further engages in active but asymmetric, one-sided interest rate positioning; i.e., it uses mostly bonds to affect debt maturity and does so only when the interest rate environment is favorable to lock-in interest rates by issuing longer-term bonds. Debt management is mainly driven by marketable debt rather than total debt. Issuing behavior became more regular and demand-oriented during the early 1990s when marketable and total debt increased in tandem.
Keywords: E63; H63; 330; Government debt; Government debt management; Government debt maturity